The overview of the implementation of total quality management in the Libyan construction industry - Salah , Mohamed Khalil; Abdelgalil, Abdelgalil; Said, Ilias (2008)
The current trends in the construction industry are now moving toward higher quality. Contractors are forced to upgrade the quality of their services. The implementation of total quality management (TQM) becomes necessary in the construction industry. It is actually the set of activities that are performed by the contractor for the customer satisfaction. The main reason for the introduction of the TQM in the construction industry is the knowledge level of the customer which is increasing gradually regarding to the quality issues. Therefore, this elevation in the knowledge level of the client results demand for the better quality, because in many construction projects clients often find themselves paying high prices for defective works that don’t satisfy their needs. The objectives of this paper are 1) to investigate the awareness of the contractors in Libya with regards to TQM, level of customer satisfaction and the government interventions for quality. This research was a cross sectional survey conducted in the capital of Libya Tripoli. This study found that the Libyan Government is stressing on allocation of high budget for construction, so far no importance is shown regarding to the ISO implementation. This study reflects the situation of Libyan construction industry regarding to the quality practices. The knowledge level among the Libyan construction industry is moderate and the implementation within the organisation is also at a grass root level, this is because of lack of consideration of a quality system in the Libyan construction industry. There is a need of immediate initiative by the government and the ministry of housing building and planning to stress on implementation of TQM and ISO certification within the Libyan construction industry to attain better customer services and quality construction. Libyan government can play a vital role in this regard by stressing on adopting ISO and TQM practices in Libyan construction industry. This paper also recommends suggestions for future research.